Characterisation of Xe-133 background at the IMS stations in the East Asian region: Insights based on known sources and atmospheric transport modelling. (December 2022) - Kuśmierczyk-Michulec, Jolanta; Baré, Jonathan; Kalinowski, Martin; Tipka, Anne
Abstract: Radioxenon can be produced with a high fission yield during a nuclear explosion, making it an important tracer to demonstrate the nuclear origin of an explosion. For this reason, it is continuously monitored by the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO) as part of the verification regime. Radioxenon is emitted by civil nuclear facilities, like nuclear power plants (NPPs) or isotope production facilities (IPFs), providing significant but variable contribution to the noble gas background. The discrimination between CTBT-relevant radioxenon detections and the background is then a challenging task. This work aims at estimating the radioxenon background at 8 East Asian noble gas stations of the International Monitoring Systems (IMS) (out of 26 certified and 14 others foreseen) based on known sources and atmospheric transport modelling (ATM). For the purpose of this study, the transportable system in Mutsu, Japan, was also included. The results demonstrate a predominant contribution of NPPs to the radioxenon background at most of the East Asian IMS stations, especially during summertime. In autumn, as a result of large-scale atmospheric circulation, the contribution of remote IPFs starts to dominate. In the summertime, up to 80% of the Xe-133 detections at a station may be explained by contributions from NPPs. The detections even rise to 100% in some specific cases. At some stations under investigation in this study, a transition from NPP to IPF domination is observed in September and continues during the autumn season. It has also been shown that, for some stations, simulated concentrations above the detection limit may include observable contributions from up to 19 different sources per daily sample; at the same time the sample being sensitive to 80 or more possible sources of radioxenon. This indicates that the accumulation of many weak sources can lead to a measurable result in a single air sample. This might also explain observations at very remote stations. Another important conclusion is that, despite limited knowledge about release patterns of NPPs, the agreement between simulated and measured values was good in many cases. Availability of IMS measurements allowed for validation of simulations. This comparison revealed that approximately 76% of simulated values were underestimated. Based on the paired t -test, a 95% confidence interval for the true mean difference between measurements and simulations was constructed. It was estimated that for data dominated by NPPs contribution (i.e. NPPs contribution exceeds 70%), the overall uncertainty of simulated results lies between 0.07 and 0.10 mBq/m 3 . For data dominated by IPFs contribution (i.e. IPFs contribution exceeds 70%), the uncertainty for the simulations is in the range between 0.03 and 0.12 mBq/m 3 . Highlights: NPPs are the main Xe-133 contributors to the background in East-Asia during summer. Weak Xe-133 contributions may accumulate, leading to measurable quantities in samples. The benefit of having 2 measurement systems located in relative vicinity is demonstrated. ATM simulations are validated using measured Xe-133 activity concentrations.